Method for preparing multi-element uniformly-doped sodium ferric sulfate porous sodium battery positive electrode material by using mixed alcohol precipitation method

By mixing sodium ferrosulfate material with the sulfate to be doped at room temperature, the raw materials are difficult to mix and impure products during the preparation process of sodium ferrosulfate material in the prior art. The preparation of high-purity, low-defect, uniformly doped iron sulfate porous sodium electropositive electrode material has been achieved, and the electrochemical performance and production efficiency have been improved.

CN119503889AActive Publication Date: 2025-02-25HUNAN NORMAL UNIVERSITY

Patent Information

Application Number
CN202411676852.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

It is difficult to effectively prepare high-purity, low-defect, uniformly doped iron sulfate porous sodium electropositive electrode materials, and traditional methods have problems such as difficulty in mixing raw materials, impure products, and long preparation periods.

Method used

Ferrous sulfate heptahydrate, anhydrous sodium sulfate and element sulfate to be doped in deionized water were mixed by mixing alcohol analysis method at room temperature, and then a carbon source solution was added, and multi-element uniformity was prepared after stirring reaction and sintering treatment. Doped sodium iron sulfate material.

Benefits of technology

The uniform doping of sodium iron sulfate material is achieved, the purity and electrochemical activity of the product are improved, the production cycle is shortened, the cost is reduced, and the secondary particles and pore distribution is effectively controlled.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005147245620000011
    Figure HDA0005147245620000011
  • Figure HDA0005147245620000012
    Figure HDA0005147245620000012
  • Figure HDA0005147245620000021
    Figure HDA0005147245620000021
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a method for preparing a multi-element uniformly-doped sodium ferric sulfate porous sodium battery positive electrode material by a mixed alcohol precipitation method, which is characterized by comprising the following steps of: weighing element sulfate to be doped and ferrous sulfate heptahydrate according to a molar ratio of (0.1-15%): 1; the method comprises the following steps: preparing a mixed alcohol solution containing a carbon source, weighing anhydrous sodium sulfate with a corresponding molar weight, dissolving the anhydrous sodium sulfate in deionized water to form a uniform mixed solution, adding the mixed solution into the mixed alcohol solution containing the carbon source, carrying out a stirring reaction at room temperature for a certain period of time (1 min to 4 h), separating slurry to obtain powder, and collecting and storing a filtrate for subsequent recycling. And sintering the powder to prepare the multi-element uniformly-doped sodium ferric sulfate type material. The method disclosed by the invention can effectively solve the problems of difficult uniform mixing of raw materials, impure product, many defects, non-uniform distribution of doped elements, and difficult regulation and control of secondary particle and pore distribution of the product in the traditional synthesis and modification process, and ultimately improves the electrochemical performance of the doped sodium ferric sulfate positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a multi-element uniformly doped sodium ferric sulfate porous sodium positive electrode material by a mixed alcohol precipitation method, a doped sodium ferric sulfate material prepared by the method, and a battery comprising the doped sodium ferric sulfate material. Background Art

[0002] In recent years, with the rapid development of the new energy industry, lithium-ion batteries are facing the problem of rising costs year by year due to the uneven distribution of lithium mines and the difficulty of mining. There is an urgent need to find suitable substitutes. Sodium has attracted a lot of attention because its physical and chemical properties are similar to those of lithium, and its raw materials are abundant and widely available, and the cost of raw materials is low. Sodium-ion battery positive electrode materials can currently be divided into three categories: layered oxides, polyanionic compounds, and Prussian blue analogs. Polyanionic compounds have a stable crystal structure and three-dimensional sodium ions (Na + ) diffusion channel, showing the characteristics of high voltage, high rate and low temperature working performance and excellent cycle performance. In particular, sodium iron sulfate-based polyanion positive electrode materials have the advantages of lower raw material cost, low synthesis temperature and less energy consumption compared with other polyanion materials.

[0003] The survey found that the common synthesis and modification methods of sodium iron sulfate materials are to mix iron source, sodium source, sulfur source and carbon source through solid phase ball milling (CN118676332A, CN118676332A, CN116692950A) or sand milling (CN118479548A). This method effectively reduces the preparation cost of sodium iron sulfate materials in the actual production process, but it is difficult to avoid the problems of difficult mixing of raw materials during solid phase mixing, low product purity, many defects, and uncontrollable secondary particle and pore distribution. In recent years, there are also some reports of preparing sodium iron sulfate materials by spray drying (CN118117067A), sol-gel method (CN118164458A), microwave solvent thermal method (CN116553621B), etc. The essence of spray drying is heating and dehydration. The solubility of different sulfates varies greatly with temperature. The solid obtained is not a homogeneously mixed sulfate and the acidic solution is more corrosive to the spray inlet and outlet pipes; the sol-gel method and microwave solvent thermal method consume more energy during implementation. In summary, there is no patent or literature report that a variety of element-doped sodium iron sulfate materials with few product defects, high purity, and controllable secondary particles and pore distribution are obtained by simple, low-energy room temperature solid-liquid separation. In view of the shortcomings of the prior art, the present invention first reports that sodium source, iron source, sulfur source, carbon source and a variety of sulfates to be doped are treated by simple room temperature mixing alcohol precipitation, and a variety of element-doped sodium iron sulfate materials are prepared simply and efficiently. Porous sodium positive electrode materials. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and to provide a method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material in a simple and efficient manner, a doped sodium iron sulfate material prepared by the method, and a battery comprising the doped sodium iron sulfate material. The present invention prepares a uniform doped sodium iron sulfate mixture, has few defects, has a high product purity, has controllable secondary particle and pore distribution, and significantly improves electrochemical activity and rate performance.

[0005] The method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by a mixed alcohol precipitation method is characterized by comprising the following steps:

[0006] ① Under room temperature, ferrous sulfate heptahydrate, anhydrous sodium sulfate, and sulfate of the element to be doped are mixed in deionized water in a certain proportion and stirred to form a mixed solution A;

[0007] ② Dissolve a certain amount of carbon source in the mixed alcohol and mix evenly to form solution B, so that solution B and mixed solution A are in a certain volume ratio;

[0008] ③ Add the mixed solution A to the mixed solution B, and stir at room temperature for a period of time to obtain a slurry;

[0009] ④ Separating the slurry obtained in step ③ to obtain a filtrate (supernatant) and a powder, performing subsequent operations on the powder, and collecting and storing the filtrate for subsequent recycling;

[0010] ⑤ After sintering the powder in step ④ in an inert atmosphere for a period of time, a sodium iron sulfate material uniformly doped with multiple elements is obtained.

[0011] Furthermore, in step ①, the room temperature range is 20-30° C., and the molar ratio of anhydrous sodium sulfate to ferrous sulfate heptahydrate is (1:1, 2.4:1.8, 2.5:1.75, 2.6:1.7);

[0012] Furthermore, in step ①, the molar ratio of the total of the multiple doping element sulfates to the ferrous sulfate heptahydrate is (0.1% to 15%: 1), and the element sulfates to be doped include several of nickel sulfate hexahydrate, magnesium sulfate, manganese sulfate monohydrate, copper sulfate, hydrated vanadium sulfate, ammonium cobalt sulfate hexahydrate, zinc sulfate heptahydrate, lithium sulfate monohydrate, potassium sulfate, and calcium sulfate dihydrate;

[0013] Furthermore, in step ②, the mixed alcohol includes several of anhydrous ethanol, methanol, ethylene glycol, glycerol, and n-butanol, the carbon source includes one or more of glucose, citric acid monohydrate, ascorbic acid, Super P, graphene, carbon nanotubes, PVP, and sucrose, and the volume ratio of the mixed solution A to the solution B is (1:1-10);

[0014] Furthermore, the stirring time in step ③ is 1 min to 4 h;

[0015] Furthermore, in step ⑤, the inert atmosphere is a mixture of argon and hydrogen (the volume of hydrogen is 1% to 5%) and high-purity nitrogen, the sintering temperature is 300 to 400° C., and the sintering time is 2 h to 12 h;

[0016] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0017] (1) The method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by the mixed alcohol precipitation method provided by the present invention does not require long-term mixing during the implementation process, thereby shortening the production cycle and reducing the production cost;

[0018] (2) The method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by the mixed alcohol precipitation method provided by the present invention can achieve uniform doping of multiple doping elements, thereby significantly improving the electrochemical performance of the prepared sodium iron sulfate material;

[0019] (3) The present invention provides a method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by a mixed alcohol precipitation method. During the implementation process, the problems of difficult mixing of raw materials, impure products, many defects, uneven distribution of doping elements, long preparation cycle, and difficult control of product secondary particles and pore distribution in the traditional solid phase mixing process are effectively solved;

[0020] (4) The method for preparing multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by the mixed alcohol precipitation method provided by the present invention avoids the loss of raw materials in the traditional production process during implementation, and effectively improves the product yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Shown is an XRD diffraction pattern of a multi-element uniformly doped sodium iron sulfate material prepared according to an embodiment of the present invention.

[0022] Figure 2 Shown is a SEM image of a multi-element uniformly doped sodium iron sulfate material prepared according to an embodiment of the present invention.

[0023] Figure 3 Shown is a SEM-EDX image of a multi-element uniformly doped sodium iron sulfate material prepared according to an embodiment of the present invention.

[0024] Figure 4 Shown is a Raman curve diagram of a multi-element uniformly doped sodium iron sulfate material prepared according to an embodiment of the present invention.

[0025] Figure 5The XPS graph of the multi-element uniformly doped sodium iron sulfate material prepared according to one embodiment of the present invention is shown.

[0026] Figure 6 Shown is a first cycle charge and discharge curve diagram at room temperature and -50°C low temperature of a multi-element uniformly doped sodium iron sulfate material prepared according to an embodiment of the present invention.

[0027] Figure 7 Shown is a CV curve diagram of a multi-element uniformly doped sodium iron sulfate material prepared according to an embodiment of the present invention.

[0028] Figure 8 Shown is a capacity retention graph of a multi-element uniformly doped sodium iron sulfate material prepared according to an embodiment of the present invention.

[0029] Fig. 9 Shown is a rate performance diagram of a multi-element uniformly doped sodium iron sulfate material prepared according to an embodiment of the present invention.

[0030] Fig.10 Shown is a nitrogen adsorption-desorption curve diagram of a multi-element uniformly doped sodium iron sulfate material prepared according to an embodiment of the present invention, and the inset diagram is a pore size distribution diagram. Specific implementation methods

[0032] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0033] The first aspect of the present invention provides a method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by a mixed alcohol precipitation method, comprising the following steps:

[0034] Embodiment 1

[0035] The invention discloses a method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by a mixed alcohol precipitation method. The specific operation scheme is as follows: 45.4407g of ferrous sulfate heptahydrate, 17.7553g of sodium sulfate, 0.6275g of lithium sulfate monohydrate, and 0.5525g of manganese sulfate monohydrate are weighed and dispersed in 200mL of deionized water, which is called solution A; 4.5441g of citric acid monohydrate, 0.4544g of ascorbic acid, and 1.896g of carbon nanotubes are weighed and dispersed in 500mL of anhydrous ethanol / ethylene glycol mixed alcohol (ethylene glycol accounts for 20% by volume), which is called solution B; solution A is slowly added to the high-speed stirring solution B at 25°C, and mixed for 6 minutes to obtain a slurry, and the slurry is filtered to obtain a filtrate and powder, and the filtrate is collected and stored for subsequent recycling; the powder is sintered at 350°C for 5h in an argon-hydrogen mixed atmosphere (hydrogen accounts for 2% by volume) to obtain a lithium and manganese dual-element co-doped sodium iron sulfate material. The specific surface area of ​​the material is 11.8621m 2 ·g -1 , pore size is 28.8041nm, 0.1C discharge capacity is 107.34mAh·g -1 , 1C capacity is 105.53mAh·g -1 The 50-cycle retention rate is 89.02%, and the 1C discharge capacity at -50°C is 74.83 mAh g -1 .

[0036] Embodiment 2

[0037] The present invention discloses a method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by a mixed alcohol precipitation method. The specific operation scheme is: weigh 48.652g of ferrous sulfate heptahydrate, 17.7553g of sodium sulfate, 0.429g of nickel sulfate hexahydrate, and 0.197g of magnesium sulfate and disperse them in 300mL of deionized water, which is called solution A; weigh 4.865g of citric acid monohydrate, 0.487g of glucose, and 2.019g of carbon nanotubes and disperse them in 600mL of anhydrous ethanol / glycerol mixed alcohol (the volume ratio of glycerol is 20%), which is called solution B; slowly add solution A to the high-speed stirred solution B at 25°C, mix for 5min to obtain slurry, filter the slurry to obtain filtrate and powder, collect and store the filtrate for subsequent recycling; sinter the powder at 350°C for 4h in a high-purity nitrogen atmosphere to obtain a nickel-magnesium dual-element co-doped sodium iron sulfate material. The specific surface area of ​​the material is 11.9828m 2 ·g -1 The pore size is 28.8371nm, and the 0.1C discharge capacity at room temperature is 109.66mAh·g -1 , 1C capacity is 106.76mAh·g -1The 50-cycle retention rate is 86.64%, and the 1C discharge capacity at -50°C is 75.10 mAh g -1 .

[0038] Embodiment 3

[0039] The invention discloses a method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by a mixed alcohol precipitation method. The specific operation scheme is: weigh 69.5025g of ferrous sulfate heptahydrate, 17.7553g of sodium sulfate, 0.8609g of calcium sulfate dihydrate, and 0.8713g of potassium sulfate and disperse them in 400mL of deionized water, which is called solution A; weigh 6.9503g of citric acid monohydrate, 0.695g of sucrose, and 2.019g of carbon nanotubes and disperse them in 600mL of anhydrous ethanol / methanol mixed alcohol (methanol accounts for 15% by volume), which is called solution B; slowly add solution A to the high-speed stirred solution B at 25°C, mix for 10min to obtain a slurry, filter the slurry to obtain a filtrate and a powder, collect and store the filtrate for subsequent recycling; sinter the powder at 350°C for 6h in a high-purity nitrogen atmosphere to obtain a calcium and potassium double-element co-doped sodium iron sulfate material. The specific surface area of ​​the material is 12.0121m 2 ·g -1 , pore size is 28.8441nm, 0.1C discharge capacity is 102.37mAh·g -1 , 1C capacity is 100.66mAh·g -1 The 50-cycle retention rate is 85.44%, and the 1C discharge capacity at -50°C is 74.19 mAh g -1 .

[0040] Embodiment 4

[0041] The invention discloses a method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by a mixed alcohol precipitation method. The specific operation scheme is as follows: weigh 52.1269g of ferrous sulfate heptahydrate, 17.755g of sodium sulfate, 2.9658g of zinc sulfate heptahydrate, and 3.7052g of ammonium cobalt sulfate hexahydrate and disperse them in 300mL of deionized water, which is called solution A; weigh 5.2127g of citric acid monohydrate, 0.5212g of ascorbic acid, and 2.019g of carbon nanotubes and disperse them in 720mL of anhydrous ethanol / glycerol mixed alcohol (glycerol accounts for 20% by volume), which is called solution B. At 30°C, solution A is slowly added to the high-speed stirred solution B, and mixed for 30 minutes to obtain a slurry. The slurry is filtered to obtain a filtrate and powder, and the filtrate is collected and stored for subsequent recycling; the powder is sintered at 350°C for 6h in a high-purity nitrogen atmosphere to obtain a zinc and cobalt dual-element co-doped sodium iron sulfate material. The specific surface area of ​​the material is 12.0071m 2 ·g -1, pore size is 28.8393nm, 0.1C discharge capacity is 101.17mAh·g -1 , 1C capacity is 99.62mAh·g -1 The 50-cycle retention rate is 88.63%, and the 1C discharge capacity at -50°C is 73.87 mAh g -1 .

[0042] Embodiment 5

[0043] The invention discloses a method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by a mixed alcohol precipitation method. The specific operation scheme is as follows: weigh 52.1269g of ferrous sulfate heptahydrate, 17.755g of sodium sulfate, 0.4682g of copper sulfate pentahydrate, and 0.2193g of hydrated vanadium sulfate, dispersed in 200mL of deionized water, called solution A; weigh 5.2127g of citric acid monohydrate, 0.5212g of ascorbic acid, 3.6g of PVP, and 2.019g of carbon nanotubes, dispersed in 720mL of anhydrous ethanol / n-butanol mixed alcohol (n-butanol accounts for 10% by volume), called solution B, slowly add solution A to the high-speed stirring solution B at 25°C, mix for 5min to obtain slurry, filter the slurry to obtain filtrate and powder, collect and store the filtrate for subsequent recycling; sinter the powder at 350°C for 6h in a high-purity nitrogen atmosphere to obtain a copper and vanadium dual-element co-doped sodium ferric sulfate material. The specific surface area of ​​the material is 12.0145m 2 ·g -1 , pore size is 28.8478nm, 0.1C discharge capacity is 104.62mAh·g -1 , 1C capacity is 102.21mAh·g -1 The 50-cycle retention rate is 89.73%, and the 1C discharge capacity at -50°C is 74.77 mAh g -1 .

Claims

1. A method for preparing a multi-element uniformly doped sodium iron sulfate porous sodium positive electrode material by a mixed alcohol precipitation method, characterized in that: The following steps are involved: ① Under room temperature, ferrous sulfate heptahydrate, anhydrous sodium sulfate, and sulfate of the element to be doped are mixed in deionized water in a certain proportion and stirred to form a mixed solution A; ② Dissolve a certain amount of carbon source in the mixed alcohol and mix evenly to form solution B, so that solution B and mixed solution A are in a certain volume ratio; ③ Add the mixed solution A to the mixed solution B, and stir at room temperature for a period of time to obtain a slurry; ④ Separating the slurry obtained in step ③ to obtain a filtrate (supernatant) and a powder, performing subsequent operations on the powder, and collecting and storing the filtrate for subsequent recycling; ⑤ After sintering the powder in step ④ in an inert atmosphere for a period of time, a sodium iron sulfate material uniformly doped with multiple elements is obtained.

2. The method according to claim 1, characterized in that: The room temperature range in step ① is 20-30° C., and the molar ratio of the sodium sulfate and the ferrous sulfate heptahydrate is (1:1, 2.4:1.8, 2.5:1.75, 2.6:1.7).

3. The method according to claim 1, characterized in that: The molar ratio of the various doping element sulfates to ferrous sulfate heptahydrate described in step ① is (0.1% to 15%: 1), and the various doping element sulfates include nickel sulfate hexahydrate, magnesium sulfate, manganese sulfate monohydrate, copper sulfate, hydrated vanadium sulfate, ammonium cobalt sulfate hexahydrate, zinc sulfate heptahydrate, lithium sulfate monohydrate, potassium sulfate, and calcium sulfate dihydrate.

4. The method according to claim 1, characterized in that: The mixed alcohol in step ② includes several of anhydrous ethanol, methanol, ethylene glycol, glycerol, and n-butanol, the carbon source includes one or several of glucose, citric acid monohydrate, ascorbic acid, Super P, graphene, carbon nanotubes, and PVP, and the volume ratio of the mixed solution A to solution B is (1:1-10).

5. The method according to claim 1, characterized in that: The stirring time in step ③ is 1 min to 4 h.

6. The method according to claim 1, characterized in that: In step ⑤, the inert atmosphere is a mixture of argon and hydrogen (hydrogen accounts for 1% to 5% of the volume) and high-purity nitrogen, the sintering temperature is 300 to 400° C., and the sintering time is 2 h to 12 h.

Citation Information

Patent Citations

  • Sodium ferric sulfate, its preparation method and application

    CN116553621B

  • Preparation method and equipment of sodium ferric sulfate polyanion positive electrode material

    CN116692950A

  • Modified sodium ferric sulfate positive electrode material and preparation method thereof, and secondary battery

    CN118117067A

  • Preparation method of simple carbon-coated anion-doped sodium ferric sulfate as sodium ion battery positive electrode material

    CN118164458A

  • Carbon composite sodium ferric sulfate positive electrode material as well as preparation method and application thereof

    CN118479548A

Cited By

  • Method for regenerating waste ferric sodium sulfate positive electrode material by recycling high-value carbon source and PVDF (polyvinylidene fluoride)

    CN121507184A